PERENCANAAN PENDIDIKAN ISLAM BERBASIS DATA SEBAGAI INSTRUMEN KEBIJAKAN PENDIDIKAN NASIONAL - Muhammad Fauzi Ridwan; Bambang Firmansyah; Hamdu Ma'ruf (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Evidentially weak educational planning stands as one of the primary root causes of the low quality and inequity of Islamic educational services in Indonesia. Policies formulated without robust data support tend to fail in addressing the root of the problems and produce programs with minimal impact. This study aims to examine in depth the concepts, frameworks, mechanisms, and implementation challenges of data-driven Islamic education planning as an instrument of national education policy. The approach employed is qualitative with a library research method that systematically collects, analyzes, and synthesizes primary literature sources consisting of the latest reference books and reputable national and international scientific journal articles. The analysis was conducted through three main stages, namely data reduction, data presentation, and conclusion drawing. The findings indicate that effective data-driven Islamic education planning requires the availability of a reliable educational management information system infrastructure, adequate analytical capacity of planning human resources, a responsive feedback mechanism between field data and the policy-making process, as well as the integration of Islamic values as an ethical compass throughout all stages of planning. The data-driven planning model formulated in this study positions data integrity, process inclusivity, and orientation toward the welfare of the community (kemaslahatan umat) as three main pillars that distinguish it from conventional planning models.